Strengthening Children’s Advertising Defenses: The Effects of Forewarning of Commercial and Manipulative Intent - Rozendaal, Esther; Buijs, Laura; Reijmersdal, Eva A. van (Frontiers in Psychology, 2016)
This study investigated whether a forewarning of advertising’s intent can increase children’s (N = 159, 8-10 years old) defenses against television commercials to lower their desire for advertised products. Two different forewarnings were tested, one for advertising’s commercial intent or warning for the promotional nature, and one for advertising’s manipulative intent or warning for the deceptive nature. Results showed that only the warning of manipulative intent prior to advertising exposure was successful in increasing children’s advertising defenses. This forewarning activated children’s attitudinal advertising literacy (i.e., skepticism towards the commercial), which in turn led to lower advertised product desire. The forewarning of commercial intent was not effective in strengthening children’s advertising defenses. These findings have important implications for interventions that aim to lower children’s desire for (unhealthy) advertised products by activating their advertising literacy.